2013
DOI: 10.1161/jaha.112.000068
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anxiety and Depression With All‐Cause Mortality in Individuals With Coronary Heart Disease

Abstract: BackgroundDepression has been related to mortality in coronary heart disease (CHD) patients, but few studies have evaluated the role of anxiety or the role of the co‐occurrence of depression and anxiety. We examined whether anxiety is associated with increased risk of mortality after accounting for depression in individuals with established CHD.Methods and ResultsThe cohort was composed of 934 men and women with confirmed CHD (mean age, 62±11 years) who completed the Hospital Anxiety and Depression scale (HADS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
179
5
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(204 citation statements)
references
References 64 publications
11
179
5
9
Order By: Relevance
“…Although the difference in the correlations may not be clinically significant, it suggests that there was a comorbidity of depression and anxiety in our sample. This may have two not mutually exclusive explanations: a) The comorbidity of depression and anxiety is evident worldwide (Kessler et al, 2015) and in the Arabic population specifically (Al-Turkait et al, 2011;Belzer and Schneier, 2004;Ohaeri et al, 2010) and b) there is evidence that depression is correlated to anxiety in patients with heart disease (Frasure-Smith et al, 1995;Watkins et al, 2013) and this comorbidity can affect between 21% to 26% of the patients (Doering et al, 2010;Frasure-Smith and Lesperance, 2008). Both explanations support the validity of the A-CDS.…”
mentioning
confidence: 97%
“…Although the difference in the correlations may not be clinically significant, it suggests that there was a comorbidity of depression and anxiety in our sample. This may have two not mutually exclusive explanations: a) The comorbidity of depression and anxiety is evident worldwide (Kessler et al, 2015) and in the Arabic population specifically (Al-Turkait et al, 2011;Belzer and Schneier, 2004;Ohaeri et al, 2010) and b) there is evidence that depression is correlated to anxiety in patients with heart disease (Frasure-Smith et al, 1995;Watkins et al, 2013) and this comorbidity can affect between 21% to 26% of the patients (Doering et al, 2010;Frasure-Smith and Lesperance, 2008). Both explanations support the validity of the A-CDS.…”
mentioning
confidence: 97%
“…Also, in another study, persistence of comorbid depression and anxiety was noted to significantly contribute to mortality (32). In addition, a recent 3-year follow-up study revealed that anxiety and depression were both independently associated with the increased risk of mortality, and cooccurrence of these conditions showed an additive 3-fold increased risk (33).…”
Section: Anxiety In Chd and Long-term Cardiac Outcomesmentioning
confidence: 88%
“…Состояние дистресса, которое неизбежно испытывает больной, перенесший технически сложное и длительное опера-тивное вмешательство, может сопровождаться аффек-тивными расстройствами, которые не только в 2-3 раза повышают риск смерти и усугубляют клиническое тече-ние послеоперационного периода, но и снижают при-верженность пациента к врачебным рекомендациям [7,8]. Расстройства тревожно-депрессивного спектра также могут существенно ухудшать качество жизни больных [9], значительно снижая, тем самым, эффект дорогосто-ящего оперативного лечения.…”
Section: Quality Of Life and Psycho-cognitive Condition In Patients Aunclassified
“…Нарастание когнитивных расстройств, напротив, приводило к снижению тревоги, что под-тверждается выявленной отрицательной корреляци-онной связью между показателями шкал MMSE и HARS (r=-0,35; р<0,05). Как и у прочих больных с сердечно-сосудистыми заболеваниями [8] у иссле-дуемых пациентов отмечалась коморбидность тре-воги и депрессии (r=0,91; p<0,05). Тревога и депрес-сия (ГШТД) закономерно снижали удовлетворен-ность больных, перенесших АКШ, своим КЖ (r=-0,53; p<0,05, r=-0,52; p<0,03).…”
Section: материал и методыunclassified